Exploring Global Trends and Innovations in Educational Technology: A Bibliometric Analysis of Emerging Paradigms and Key Contributions - Tua, Sahat (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2024)
This study aims to investigate the latest trends in educational technology and identify emerging innovations in the scientific literature using the Bibliometric Analysis method. The background of the research confirms the importance of an in-depth understanding of the latest developments in technology-based education, given the rapid changes taking place in this domain. The results highlight the significant influence of countries such as the United States, Russia, Brazil, and China in initiating and realizing educational technology innovations. In addition, the study identified several significant journals, such as "Educational Technology Research," "Education and Information," and "Journal of Dental Education" that play a crucial role in documenting and disseminating information about the latest developments in educational technology. Another interesting finding is the emergence of the keyword 'gaming' as an innovation that increasingly dominates the educational technology literature, showing a trend towards game-based play and learning approaches in educational contexts. The conclusion of this study provides valuable insights for practitioners and researchers in the field of educational technology. This information can inform educational strategies, develop innovative projects, and direct future research to better understand and utilize educational technology in the learning process.